Effects of Drug Abuse on Academic Performance Among Undergraduate Students in Federal University Wukari, Taraba State - Abdulmudallib, Ibrahim; Thomas, Namegh Sabastine; Alao, Olateju Bamigbala (African Journal of Sciences and Traditional Medicine, 2024)
This paper conducted a questionnaire survey at the Federal University of Wukari on the effects of drug abuse on academic performance among undergraduate students. The study aimed to investigate the effects of drug abuse on academic performance among undergraduate students. Descriptive statistics and an independent two-sample t-test were used for the data analysis. The results revealed significant differences in academic performance between drug abuse and non-drug abuse groups, with nicotine emerging as the most commonly abused drug among the surveyed students. The findings of this study highlight the need for attention to substance abuse issues among undergraduate students. While drug abuse was preval_ent, its direct impact on academic performance appeared to be nuanced. The study therefore recommends the need to implement targeted substance abuse prevention programs tailored to the specific needs and challenges faced by undergraduate students.